Skin tear risks associated with aged care residents: a cross-sectional study - Rayner, Robyn; Carville, Keryln; Leslie, Gavin; Dhaliwal, Satvinder (Cambridge Publishing, 2018)
Background: To describe the profile of aged care residents and to examine those variables that were associated with skin tears. Method: A representative sample of 200 elderly residents were recruited into this cross-sectional study, which was conducted between February and December 2014 from four aged care facilities in Western Australia. The resident's history of skin tears over the preceding 12-months was compared with their demographics (age, gender, place of birth) and a. broad range of clinical characteristics including: body mass index, comorbidities, medications, smoking history, falls, and personal skin characteristics (purpura, ecchymosis, bruising uneven pigmentation, pseudoscars). Results: A history of skin tears was documented for 101 (50.5%) residents during the preceding 12-months. Residents with a skin tear history were significantly older, more likely to have a skin tear on initial assessment, had a lower Braden Scale score and a lower Braden sub-score for mobility, were at higher risk of falling, had osteoporosis, used a corticosteroid inhaler, and displayed both skin purpura (s 20 mm.) and ecchymosis (:2: 20 mm.). Conclusions: Aged care residents are at substantial risk of skin tears. Identification of factors associated with skin tears aids better understanding of risk factors and enables more effective targeted preventive strategies.